Gold Nanoparticles : An Introduction to Synthesis, Properties and Applications - Voliani, Valerio (De Gruyter, 2020)
Gold nanoparticles provide a platform for the development of new and efficient diagnostic and therapeutic tools.This book offers a general guide to the synthesis and coating of gold nanoparticles. It describes the links between optical features and geometries of gold nanoparticles and provides a readily comprehensible connection in all the chapters between the geometry of gold nanoparticles and their final applications.